Proliferating cell nuclear antigen (PCNA) and nucleolar organiser regions in Hodgkin's disease: correlation with morphology. Issue 5 (May 1993) - Freeman, J; Kellock, D B; Yu, C C; Crocker, J; Levison, D A; Hall, P A
Abstract : AIM–To define the distribution of proliferating cell nuclear antigen (PCNA) and silver staining nucleolar organiser regions (AgNORs) in Hodgkin's disease. METHODS–PCNA was shown in a series of 34 cases of Hodgkin's disease using immunohistochemical methods. In a second series of 46 cases the AgNOR technique for interphase nucleolar organiser regions was studied. Both series comprised routinely fixed and processed paraffin wax sections of three main Rye subtypes. RESULTS–In all cases, regardless of Rye subtype, most Sternberg-Reed cells and mononuclear Hodgkin cells showed nuclear PCNA immunoreactivity and such cells had 15 or more AgNOR sites. The Hodgkin cells had, in general, about half the number of AgNORs seen in Sternberg-Reed variants. CONCLUSIONS–These data support the notion that Hodgkin's disease can be regarded as a high grade lymphoma, the large Hodgkin's and Sternberg-Reed cells being the (PCNA positive and AgNOR rich) neoplastic elements with high proliferative capacity. A smaller proportion of the associated cells also showed evidence of proliferation.